Kaidah Hafalan Al-Quran Pada Madrasah Tahfiz Annur Markaz Yala Dan Madrasah Darussalam Rangek Narattiwat Di Thailad Selatan - Ahmadzakee Mahama; Phaosan Jehwae (Wardah, 2017)
This paper purpose to examine the rules of recitation of the al-Qur’an in Southern Thailand at Madrasah Annur Markaz Yala and Madrasah Darussalam. The author tries to see which rules are more practical to be practiced in the process of memorizing the al-Qur’an between the two rules. This study looks at current developments either at the stage of the academic Madrasah or in the religious section of each student in each method of guiding to memorize the al-Qur’an with the same time period of purpose as to memorize what is memorized. In this study is to see the good rules to use in order to give birth to the memorizers of the al- Qur'an are really good in terms of memorization. It will also be discussed about the law of memorizing the al-Qur’an, the advantages memorization of the al-Qur’an and the important of memorizing the al-Qur’an which in this study the authors will analyze and determine the student in one madrasah as many as 60 people with a share of 10 juz, 20 juz and 30 juz .